2018
DOI: 10.1038/s41598-018-22986-3
|View full text |Cite
|
Sign up to set email alerts
|

First insights of peptidoglycan amidation in Gram-positive bacteria - the high-resolution crystal structure of Staphylococcus aureus glutamine amidotransferase GatD

Abstract: Gram-positive bacteria homeostasis and antibiotic resistance mechanisms are dependent on the intricate architecture of the cell wall, where amidated peptidoglycan plays an important role. The amidation reaction is carried out by the bi-enzymatic complex MurT-GatD, for which biochemical and structural information is very scarce. In this work, we report the first crystal structure of the glutamine amidotransferase member of this complex, GatD from Staphylococcus aureus, at 1.85 Å resolution. A glutamine molecule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 52 publications
2
16
0
Order By: Relevance
“…1 ). As previously postulated 19 and recently shown 24 , GatD exhibits a class-I glutamine amidotransferase-like fold. A DALI search 25 identifies the enzymes HisH, PdxT and PurQ from Thermotoga maritima as the closest structural homologs (Z-values of 17.4, 15.8 and 15.0, respectively).…”
Section: Resultssupporting
confidence: 68%
“…1 ). As previously postulated 19 and recently shown 24 , GatD exhibits a class-I glutamine amidotransferase-like fold. A DALI search 25 identifies the enzymes HisH, PdxT and PurQ from Thermotoga maritima as the closest structural homologs (Z-values of 17.4, 15.8 and 15.0, respectively).…”
Section: Resultssupporting
confidence: 68%
“…The corresponding residues in S. aureus GatD are Cys94-His189-Glu19. Glycine substitution of Cys94 in S. aureus GatD abolished amidation of lipid II 4 , and substitution of either Cys94 or His189 by alanine suppressed a residual glutaminase activity in the absence of MurT 38 . The glutamate of the triad in canonical class I glutaminases is highly conserved, two residues downstream of the catalytic histidine in sequence, but its catalytic role is uncertain as its replacement with a non-acidic residue had minor effect on the glutaminase activity of the human γ-glutamyl hydrolase or the Escherichia coli carbamoyl phosphate synthase 39 , 40 .…”
Section: Resultsmentioning
confidence: 97%
“…Conserved GD Arg142 at the extremity of the catalytic cleft opposite GD Cys107 appears to interact with the glutamine substrate. The corresponding Arg128 in S. aureus GatD was found to interact with a glutamine outside of the active site, and its replacement by an alanine abrogated glutaminase activity 38 . The two structures support a model in which the side chain of GD Arg142 helps to “capture” the substrate from the solution (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Combined, these results show that this residue has a pivotal role in the catalytic mechanism of the complex. The active site of GatD includes C94, H128, and MurT-D349 (21,25), and it has been shown that residues Y17 and R128 of GatD are important in blocking the substrate path to the active site, having a regulatory role in glutaminase activity (25). In the MurT-GatD structure from S. aureus, the GatD-Y17 residue can adopt two distinct conformations.…”
Section: Discussionmentioning
confidence: 99%